Taming the Machine: Comparing UAW and ILWU Responses to Automation, 1945-1972 - Watson, Daniel (2023)
This thesis is the first comparative history of rank-and-file workers in two key U.S industries – auto production and longshoring – to examine their response to automation in their workplaces in the mid-twentieth century. As these industries were two of the most heavily automated, they present an ideal comparison to draw out the often-decentralized views of the rank and file in histories of automation. Exploring the realm of responses to automation reveals these workers’ engagement with and critique of Cold War rhetoric and ideas as these individuals were at the raw end of technological development and modernization. Initially, auto and longshore workers joined their union leaders in broadly supporting the post-war drive to increase productivity and uplift the U.S. economy through automation. Rather than this process bringing about relief from physical drudgery in the workplace, it instead led to workers resisting a newfound speed-up and the crushing monotony of their jobs. With their jobs a shadow of their former selves, the rank and file lost their sense of pride and reward in their occupations, instead seeking value for work in leisure and consumption outside of the workplace. Automated work encouraged regimented and stultifying behavior which these laborers resisted by seeking to retain elements of traditional rough masculinity in the workplace. This thesis argues that these issues culminated in resistance from auto and longshore workers centering around their deteriorating mental health and the growing issues of workplace stress and loss of their previous way of life. The resistance of these workers and the successes and failures of themselves and their unions illuminates how to alleviate the mental health issues of workers facing automation in the present day when unions’ importance in industrial relations has diminished.